Tugas Dan Fungsi Badan Pertanahan Nasional Dalam Pendaftaran Tanah - Meita Djohan OE (Law Faculty of Universitas Bandar Lampung, 2015)
Task to perform registration of land in Indonesia charged to the Government by Article 19 paragraph (1) BAL determined aim is to ensure legal certainty. The approach used is a normative juridical using secondary data, data analysis performed by means of qualitative analysis. Research results Land Office in organizing tasks and functions, namely for the preparation of plans, programs, and budgets in order to implement the task of land. The advice given should hold the Land Office Legal Education and intensive socialization to the public through print and electronic media about the importance of registration of land rights to obtain proof of ownership rights in the form of certificates.